MAQSUD SHAYXZODA DRAMATURGIYASI (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2025)
Maqsud Shaykhzoda is one of the great figures of Uzbek dramaturgy, and his works are distinguished by the harmony of the national spirit, historical truth, and human values. In his plays, he skillfully reflected the inner feelings of a person, the ideas of social justice, and national independence. Shaykhzoda's dramatic works, such as "Jaloliddin Manguberdi" and "Mirzo Ulugbek," reflect the people's aspirations for freedom and progress through the fate of historical figures. His dramaturgy occupies a special place with the depth of images, the liveliness of dialogues, and the impressiveness of the stage. Therefore, Shaykhzoda is considered one of the playwrights who made a great contribution to the development of Uzbek theatrical art.